2011
DOI: 10.1164/rccm.201008-1220oc
|View full text |Cite
|
Sign up to set email alerts
|

Serum PARC/CCL-18 Concentrations and Health Outcomes in Chronic Obstructive Pulmonary Disease

Abstract: Rationale: There are no accepted blood-based biomarkers in chronic obstructive pulmonary disease (COPD). Pulmonary and activationregulated chemokine (PARC/CCL-18) is a lung-predominant inflammatory protein that is found in serum. Objectives: To determine whether PARC/CCL-18 levels are elevated and modifiable in COPD and to determine their relationship to clinical end points of hospitalization and mortality. Methods: PARC/CCL-18 was measured in serum samples from individuals who participated in the ECLIPSE (Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 27 publications
4
88
3
2
Order By: Relevance
“…The 13 metabolic analytes combined with five MetSyn clinical parameters had a sensitivity of 41%, suggesting that other pathways to lung disease remain unidentified in this analysis. Serum inflammatory biomarkers are also elevated in COPD exacerbations (49)(50)(51). We have recently reported that low a 1 -antitrypsin, elevated granulocyte-macrophage colonystimulating factor, and macrophage-derived chemokine are additional risk factors for the development of WTC-related lung injury (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…The 13 metabolic analytes combined with five MetSyn clinical parameters had a sensitivity of 41%, suggesting that other pathways to lung disease remain unidentified in this analysis. Serum inflammatory biomarkers are also elevated in COPD exacerbations (49)(50)(51). We have recently reported that low a 1 -antitrypsin, elevated granulocyte-macrophage colonystimulating factor, and macrophage-derived chemokine are additional risk factors for the development of WTC-related lung injury (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of patients with mild to moderate COPD, serum pulmonary and activation-regulated chemokine/CC-chemokine ligand-18 (PARC/CCL-18) was significantly associated with reduced FEV1, increased risk of exacerbations, and an increased BODE index (Pinto-Plata et al 2007). There is also recent evidence that elevated levels of PARC/CCL-18 are associated with increased risk of cardiovascular hospitalizations or mortality in the lung health study (LHS) cohort and with total mortality in the ECLIPSE cohort (Sin et al 2011). Circulating levels of PARC/CCL-18 have been found to be associated with acute exacerbations (Hurst et al 2006).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…10,11,38 CCL-18 is also associated with clinical outcomes, including cardiovascular morbidity, overall mortality and response to treatment. 38,39 However, it is unclear what role this chemokine may play in disease pathogenesis.…”
Section: Cc-chemokine Ligand-18 (Or Pulmonary and Activation-regulatementioning
confidence: 99%
“…10,11,38 CCL-18 is also associated with clinical outcomes, including cardiovascular morbidity, overall mortality and response to treatment. 38,39 However, it is unclear what role this chemokine may play in disease pathogenesis. 38 Biomarker Panels: In addition to the hypothesisdriven research detailed in the previous section s, the use of newer high-throughput techniques has led to the discovery of a number of candidate biomarkers that are under investigation.…”
Section: Cc-chemokine Ligand-18 (Or Pulmonary and Activation-regulatementioning
confidence: 99%
See 1 more Smart Citation